(untitled) (Global Journal of Human-Social Science, 2021)
The paper examines the relevance of the Rawlsian veil of ignorant in the Nigerian quest for restructuring. Debates on restructuring has taken over the wave of Nigeria’s academic, political, social, and economic space and have left many to ethics and tribal conflicts. The paper addresses how fairly resources should be distributed and allocated; the problem of equal opportunity in Nigeria polity. This was interogated through John Rawls’s famous "theory of justice. The paper argues that for a society like Nigeria to enjoys social cooperation and sustainable restructuring amid all polarity it is surrounded with, there is a need to employ an approach that it is devoid of ethnic/tribal, socio-cultural, and political sentiment. The paper assumes that the "veil of ignorance"-behind which the principles of justice are chosen serves as a mechanism in which social and political chauvinism and polarities in the country could be addressed. For methodology, the paper employed a philosophical-expository approach to dissect the subject matter analytically and critically.